(untitled) (Religious dialogue and cooperation, 2026)
Today, the world needs more than ever for an elevation and advancement of spirituality, for a non-abuse of the sacred, so that we do not have pollution of the environment and pollution of interpersonal relationships. This article will analyze the defect of the crisis in general and the spiritual crisis in particular. As known, man, is between two decisions: to decide to sacrifice himself for the good, or to think only about the realization of his own desires, that is, to sacrifice the other to realize his desires. Therefore, the reflection of man towards the environment is an unfolding of what he has inside him. When the Qur’an defines man, it shows that he is essentially the main cause of problems, disorders, perversions, crises, etc.. This is understood from the terms with which man is defined in the Qur’an: haluan (Man was created not calm, unbearable), dhaluman jahula’ (... he is unjust, barbaric), etc.. The ecological crisis and the lack of interpersonal relationships, which above all is an after-effect of the defilement of the soul, also show the general condition of humanity and the planet, regarding the extreme threat to the natural human environment, including air, land, water, and plant and animal species. This paper will analyse the compactness and distinction between the idea and behaviour of man, with special emphasis on the believer, which reflects on the personality of man, as well as his influence on having an attitude towards others and the environment. While writing this paper, investigative and comparative methodology and analytical methods will be used to compare the various ideas written in this field with the Scriptures. So, the main point is the critical approach to attitudes of man towards others and the environment.